(untitled) (Global Journal of Human-Social Science, 2025)
The global metal scene has established itself as an imminently masculine space while also building its image as a musical scene and community where fraternity and inclusion prevail among its members the people who listen to and experience metal music Metal to the Bone in seven years of coverage highlighting the women who are part of metal scenes worldwide has attempted to reveal that this cooptation of the metal scene by the male gender persists to this day This has necessarily led to distorting the metal community s characterization of itself as a fraternity and a safe place for all Through interviews and research it reveals the gender gap in participation in metal bands and the existence of a series of barriers that prevent and do not allow women to experience metal culture safely and without obstacles